2015
DOI: 10.2139/ssrn.2580700
|View full text |Cite
|
Sign up to set email alerts
|

An Attempt to Disperse the Italian Interlocking Directorship Network: Analyzing the Effects of the 2011 Reform

Abstract: The purpose of this paper is to analyze the effects on the Italian directorship network of the corporate governance reform that was introduced in Italy in 2011 to prevent interlocking directorships in the financial sector. Interlocking directorships are important communication channels among companies and may have anticompetitive effect. We apply community detection techniques to the analysis of the networks in 2009 and 2012 to ascertain the effect of the reform. We find that, although the number of interlocki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Aside from omitted variables and simultaneity in the empirical models, reverse causality could also be an alternative explanation for statistical significance. As such, aside from using empirical techniques such as a change in board interlocks (i.e., formation and cessation of interlocks and information flow [37]) and exogenous regulatory changes (e.g., the 2011 corporate governance reform in Italy that aims to boost investor confidence by limiting director interlocks [43]), we advocate more inquiries of the subject matter that utilize diverse research methodologies. Survey studies, focus groups, experimental studies, and field studies that corroborate with empirical results would provide additional and possibly more direct insights into further understanding of director interlocks.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…Aside from omitted variables and simultaneity in the empirical models, reverse causality could also be an alternative explanation for statistical significance. As such, aside from using empirical techniques such as a change in board interlocks (i.e., formation and cessation of interlocks and information flow [37]) and exogenous regulatory changes (e.g., the 2011 corporate governance reform in Italy that aims to boost investor confidence by limiting director interlocks [43]), we advocate more inquiries of the subject matter that utilize diverse research methodologies. Survey studies, focus groups, experimental studies, and field studies that corroborate with empirical results would provide additional and possibly more direct insights into further understanding of director interlocks.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…Our results are in line with those found in the literature. While earlier studies reported on statistical properties of these networks in selected countries [27][28][29][30], more recent works analyzed the conditional deviations from randomness of the interlock network [31], and the resilience of its core with respect to policy reforms [32][33][34].…”
Section: Connectivity Patterns At Meso-and Macro-scalementioning
confidence: 99%
“…Complex network approaches and the science of networks put well in evidence the role of the links and of the underlying network topology in the propagation of contagions and cascades (Elliott et al 2014;Markose et al 2012;Varela and Rotundo 2016;White 2014). Besides the crossshareholdings, literature has examined other channels for detecting the connection among companies and their managers, posing in evidence the interlock of directorates and rich-club relationships (Cinelli 2019;Croci and Grassi 2014;D'Errico et al 2009;Drago et al 2015).…”
Section: Introductionmentioning
confidence: 99%